Heparin-induced thrombocytopenia in pregnancy: an interdisciplinary challenge—a case report and literature review. (May 2016) - Mauermann, E.; Vökt, C.; Tsakiris, D.A.; Tobler, D.; Girard, T.
Highlights: A case of heparin-induced thrombocytopenia in pregnancy is presented. Heparin alternatives for parturients are discussed. Summary of guidelines for neuraxial anesthesia in patients taking fondaparinux is presented. Abstract: Heparin-induced thrombocytopenia is a serious adverse event of anticoagulation with a high risk of thromboembolic complications. As a consequence, anticoagulants other than heparins must be administered. These may be unavailable, contraindicated during pregnancy, off-label, impractical due to short half-lives and, most importantly, may be unfamiliar to many anesthesiologists. Impaired coagulation bears the risk of adverse events following neuraxial procedures and of peripartum hemorrhage. We describe the case of heparin-induced thrombocytopenia in a 29-year-old pregnant woman at 27 weeks of gestation with severe valvular heart disease.